Use of electronic academic counseling The electronic platform - ershad a model - Moustafa BAALI; Hamza BARKAT (Social Sciences Journal, 2021)
Academic counseling is the main pillar through which students are introduced to the academic rules and regulations and assist them in their academic progress and overcome the social, psychological, health, or academic problems and difficulties they encounter.With the recent technological changes, a new challenge has emerged for academic counseling, which is the exploitation of technology in providing counseling services, which allowed the emergence of university electronic applications and platforms providing many extension services.